Dextrose gel treatment does not impair subsequent feeding. Issue 6 (23rd May 2017) - Weston, Philip J; Harris, Deborah L; Harding, Jane E
Abstract : Background: Dextrose gel is increasingly used as first-line treatment for neonatal hypoglycaemia. Treatment with 400 mg/kg previously has been reported to impair subsequent feeding. We sought to determine if the recommended dose of 200 mg/kg altered feeding. Methods: Hypoglycaemic babies were randomised to 200 mg/kg dextrose gel or placebo and fed. Prefeed alertness, quality and duration of breast feeding, and the volume of formula taken were assessed on the next feeding. Results: Prefeed alertness scores were similar in babies (n=211) treated with dextrose or placebo gel (124 episodes, OR=1.30 (95% CI 0.62 to 2.77), p=0.49). Breastfed babies were more likely to have good feeding scores after dextrose gel (160 episodes, OR=3.54 (95% CI 1.30 to 9.67), p=0.01) but similar breastfeeding duration (57 episodes, median (range) 20 (3–90) vs 25 (2–80) min, p=0.62). Formula volumes taken were also similar (24 episodes, median (range) 4.6 (2.2–11.3) vs 6.4 (2.0–8.9) mL/kg, p=0.30). Conclusions: Treating hypoglycaemic babies with dextrose gel 200 mg/kg does not depress subsequent feeding and may improve breastfeeding quality. Trial registration number: ACTRN 12608000623392.